2020
DOI: 10.28945/4628
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Quality of E-Learning During the COVID-19 Pandemic from the Perspective of Higher Education Students

Abstract: Aim/Purpose: The objective of the research was to study the relationship of seven independent factors: administrative support, course content, course design, instructor characteristics, learner characteristics, social support, and technical support on quality of e-learning in higher education during the COVID-19 pandemic. Further, the study analyzes the moderating effect(s) of gender and level of the course on the quality of e-learning in higher education during the COVID-19 pandemic. objective of the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 66 publications
0
37
0
3
Order By: Relevance
“…Furthermore, educational technology enables the teachers to access the students at any time across boundaries and vice versa. In similar note, online learning also supports the students in attending the classes during their free time even they are at any other work (Elumalai, et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, educational technology enables the teachers to access the students at any time across boundaries and vice versa. In similar note, online learning also supports the students in attending the classes during their free time even they are at any other work (Elumalai, et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…The studies were also categorised according to their sample size. While 25.2% of the studies can be considered large, with more than 400 participants, including a number of institutional (e.g., Alturise, 2020) and international (e.g., Aristovnik et al, 2020;Elumalai et al, 2020) surveys, but particularly comprised of national surveys (e.g., Wang, Zhang, & Ye, 2020), 16.3% of studies in the review had sample sizes of up to 25 participants (see Appendix E). This is in stark comparison to studies of K-12 teaching and learning during the pandemic, with 34% of studies focusing on 25 or fewer respondents (Bond, 2020).…”
Section: Sample Focusmentioning
confidence: 99%
“…The above perceptions and views on the possibilities of the curriculum compromise in implementing online teaching and learning during the COVID-19 new normal may be connected to the variables such as course content, social and technological support, among others (Elumalai et al, 2020;Di Pietro, 2020). The findings of Elumalai et al (2020) confirmed that there is a positive relationship between the course content, social and technological support and quality of e-learning in universities. This indicates that when there is a sudden change from the traditional teaching-learning system to the new normal, it may significantly affect the quality of curriculum implementation.…”
mentioning
confidence: 99%